2019
DOI: 10.1007/s13157-019-01217-z
|View full text |Cite
|
Sign up to set email alerts
|

Plant Community Establishment in a Coastal Marsh Restored Using Sediment Additions

Abstract: A goal of wetland restoration is the establishment of resilient plant communities that persist under a variety of environmental conditions. We investigated the role of intraspecific and interspecific variation on plant community establishment in a brackish marsh that had been restored by sediment addition. Plant growth, sediment accretion, and surface elevation change in planted, not-planted, and nearby reference sites (treatments) were compared. Four perennial macrophytes were planted: Bolboschoenus robustus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 83 publications
(103 reference statements)
1
3
0
Order By: Relevance
“…Our results complement previous studies by demonstrating that planting fast‐growing marsh species (e.g. Salicornia pacifica ) is most effective at increasing lateral spread and introducing structure to an otherwise bare landscape (Yando et al 2019; Howard et al 2020). Fast‐growing species have also been shown to increase inter‐ and intraspecific plant survival rates (Silliman et al 2015; Howard et al 2020) and increase species richness in stressful environments (Xie et al 2019 a , 2019 b ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results complement previous studies by demonstrating that planting fast‐growing marsh species (e.g. Salicornia pacifica ) is most effective at increasing lateral spread and introducing structure to an otherwise bare landscape (Yando et al 2019; Howard et al 2020). Fast‐growing species have also been shown to increase inter‐ and intraspecific plant survival rates (Silliman et al 2015; Howard et al 2020) and increase species richness in stressful environments (Xie et al 2019 a , 2019 b ).…”
Section: Discussionsupporting
confidence: 89%
“…Salicornia pacifica ) is most effective at increasing lateral spread and introducing structure to an otherwise bare landscape (Yando et al 2019; Howard et al 2020). Fast‐growing species have also been shown to increase inter‐ and intraspecific plant survival rates (Silliman et al 2015; Howard et al 2020) and increase species richness in stressful environments (Xie et al 2019 a , 2019 b ). Although some managers may caution against planting fast‐growing species like S. pacifica that can quickly dominate a marsh landscape, the short‐term disadvantage of lower plant diversity (Callaway et al 2003) may be countered by improved soil conditions from the establishment of these faster growing ecosystem engineers (Jones et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Despite reduced growth on these soils, our field observations at dredge sites confirm the natural colonization of P. australis. In a brackish marsh in the Barataria Basin of Southeast Louisiana, Howard et al 60 demonstrated that transplanted P. australis to dredge sites could rapidly spread within two-years. However, further studies are needed to estimate the extent of expansion and the time it would take for P. australis to achieve substantial vegetative cover in these newly constructed sites along the MRD.…”
Section: Discussionmentioning
confidence: 99%
“…Our eld observations con rm the natural colonization of those sites by P. australis. In addition, (Howard et al, 2020) demonstrated that transplanted P. australis to dredge sites could rapidly spread within two-years. In our current study, we had included one dredge site, Sawdust MC South, but the unexpected addition of new dredge sediments, caused the destruction of all of our plantings.…”
Section: Implications For Restorationmentioning
confidence: 99%